2021
DOI: 10.1200/go.21.00087
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Prognostic Factors in a Large Cohort of Hospitalized Cancer Patients With COVID-19

Abstract: PURPOSE Patients with cancer are at increased risk for unfavorable outcomes from COVID-19. Knowledge about the outcome determinants of severe acute respiratory syndrome coronavirus 2 infection in this population is essential for risk stratification and definition of appropriate management. Our objective was to evaluate prognostic factors for all-cause mortality in patients diagnosed with both cancer and COVID-19. METHODS All consecutive patients with cancer hospitalized at our institution with COVID-19 were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 30 publications
4
12
0
3
Order By: Relevance
“…In fact, in 1 retrospective analysis of 557 consecutive COVID-19 patients, of whom 46 had active cancer, an overall fatality rate of 50% (95% CI: 34.9-65.1) versus 20.2% (95% CI: 16.8-23.9) in patients with versus without cancer was reported, with a median OS of 14 versus 35 days, respectively [14]. Consistent results have been obtained by other researchers [15,16]. Finally, in a retrospective case-control study conducted by analyzing medical records of 2,523,920 cancer patients, patients with cancer and COVID-19 had significantly worse outcomes (hospitalization rate, 47.46%; death rate, 14.93%) compared to nononcological patients with COVID-19 (hospitalization rate, 24.26%; death rate, 5.26%) (p < 0.001) [17].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In fact, in 1 retrospective analysis of 557 consecutive COVID-19 patients, of whom 46 had active cancer, an overall fatality rate of 50% (95% CI: 34.9-65.1) versus 20.2% (95% CI: 16.8-23.9) in patients with versus without cancer was reported, with a median OS of 14 versus 35 days, respectively [14]. Consistent results have been obtained by other researchers [15,16]. Finally, in a retrospective case-control study conducted by analyzing medical records of 2,523,920 cancer patients, patients with cancer and COVID-19 had significantly worse outcomes (hospitalization rate, 47.46%; death rate, 14.93%) compared to nononcological patients with COVID-19 (hospitalization rate, 24.26%; death rate, 5.26%) (p < 0.001) [17].…”
Section: Discussionsupporting
confidence: 81%
“…In this work, we presented clinical outcomes related to SARS-CoV-2 infection in patients receiving systemic antineoplastic treatment at the coordinating center of the COICA study and reported a 9.21% death rate, with 11.84% of patients requiring O 2 therapy, 15.79% requiring to be admitted to the Hospital, and 5.26% being admitted to the ICU. These findings appear to be more favorable compared to those mentioned above [14][15][16][17]. When we explored potential predictors of COVID-19-related outcomes, we found that nonscreening-versus screening-detected SARS-CoV-2 infection was associated with significantly higher odds of death, needing O 2 therapy, being admitted to hospital as well as being admitted to ICU.…”
Section: Discussionmentioning
confidence: 72%
“…Labs such as elevated CRP, elevated creatinine, and lymphopenia were all seen in COVID-19 positive cancer patients and contributed to their poor outcomes. In a large cohort study in Brazil, lymphopenia [2.20 (1.26–3.84)], creatinine elevation [2.86 (1.40–5.84)] and CRP elevation [2.86 (1.40–5.84)] were associated with an increased risk of death and worse prognosis, likely due to an increased inflammatory state and diminished immune response ( 19 ). In our study, the findings demonstrated that older individuals, elevated CRP and creatinine are independently associated with increased risk of in-hospital mortality in cancer patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…6,16 Thirty-nine percent of patients had advanced cancer, similar to that reported in the series by Lee et al 9 in the UK and the report from Nader-Manta from Brazil. 17 T A B L E 3 Univariate analysis of risk factor for 30 days all-cause mortality among hospitalized patients with COVID-19 (N = 172) compared to the results by Kuderer, in which only 11% of patients had active or progressive neoplasia, 6 the proportion of advanced cancer was much higher.…”
Section: Discussionmentioning
confidence: 99%